Emotion Work - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (The Wiley-Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
Emotion work is usually defined as the psychological processes necessary to regulate emotions that are desired in specific private life conditions. When controlling the intensity and quality of the individual's feelings is related to the public sphere and undertaken for reasons associated with paid work it is called emotional labor. Such employment occurs in contemporary service economies where the provision of services is often related to “selling feelings,” which is mainly performed by women.
Keywords: J16; J21; 330; emotion work; employment; gender division of labor; labour market; work